The fit of competitive strategies, management accounting systems and information technology systems and its effect on business unit performances / Diana Zuhroh - Zuhroh, Diana (Penerbit UiTM (UiTM Press), 2015)
This study aims to provide empirical support for the arguments that the performance of Fit Low Cost business units is better than that of Misfit Low Cost business units and that the performance of Fit Differentiation business units is better than that of Misfit Differentiation business units. The Balanced Scorecard was used to measure the performance of business units, including their financial, customer, internal process, and learning/growth performance. A survey method was employed using a questionnaire. Nonparametric multivariate analysis of variance (Kruskal Wallis test) was used to analyze the data. The business unit of a large manufacturing company in East Java Province was used as the unit of analysis. We find that Fit Low Cost business units do not outperform Misfit Low Cost business units, while Fit Differentiation business units outperform Misfit Differentiation business units. Therefore, the results for Fit Differentiation and Fit Low Cost support and reject contingency theory, respectively. These findings strengthen contingency theory and promote its relevance in practice. Given their prevalence in actual practice, some of the current management accounting practices must be analyzed by academics and included in their classroom lecture materials.